Charaterization of patients who needed urgent obstetric hystrectomy. Cienfuegos. 2013-2015 - Yoan Hernández Cabrera; Dunia Martinez Díaz; Zoraida Montero Padrón; Maria Antonia Cabeza Poblet; Ana Beatriz Abreus Castro; Marioly Ruiz Hernández (Medisur, 2018)
Foundation: Obstetric hysterectomy is a therapeutic alternative on severe processes (hemorrhagic and/or septic) which if not solved would directly influenced in maternal morbi/mortality. Knowing about the topic allows to proceed rationally and coherently on risky situations. Objective: to charaterize the patients, series of cases who needed urgent obstetric hysterectomies in Cienfuegos 2013-2015. Methods: a descriptive study was developed, a series of cases of all the patients who were performed an obstetric hysterectomy (N=37) in the Hospital Dr. Gustavo Aldereguía Lima. Cienfuegos, from 2013 to 2015. The variables analyzed were patient age, gestational age, parity, events related to pregnancy, delivery, kind of birth and type of obstetric hysterectomy. Results: the group of patients between 31-35 years old was the most numerous, representing 40,5 % of the total. The 73% of the hysterectomized women had previous deliveries and 10 (27 %) patients were nulliparous. Uterine atony was de most frequent cause (45,9 %), mainly in the 31-35 year group (41,2 %), followed by uterine rupture and placenta accreta. The total hysterectomy without ophorectomy was the most used type(43,3 %). Conclusion: in general pregnancies arrived to the term and the atony, as in many of similar studies was the predominating indication. It was corroborated that birth by cesarean section increases the relative risk to perform a hysterectomy.